A non-shedding high-toughness anti-corrosion coating composition and its preparation method and application
By designing an anticorrosion coating composition containing phenolic epoxy resin, nanotitanium powder, silicon carbide, glass flakes and cashew phenol modified polyamine curing agent, the problem of steel flue anticorrosion material falling off under high temperature, high pressure and corrosive environments is solved, and the corrosion resistance of high adhesion and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411771329.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Existing steel flue anticorrosion materials are prone to fall off in high temperature, high pressure and corrosive environments, resulting in reduced anticorrosion effect, shortened service life, and may cause pollution to the surrounding environment.
The high-tough anticorrosion coating composition that does not fall off is prepared by uniform stirring and grinding.
The anticorrosion coating composition significantly improves adhesion and corrosion resistance under high temperature, high pressure and corrosive environments, avoids falling off, extends the service life of the steel flue, and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flue anticorrosive coating compositions, and in particular relates to a non-shedding high-toughness anticorrosive coating composition and a preparation method and application thereof. Background Art
[0002] In industrial production, steel flues are important emission channels that are exposed to high temperature, high pressure and corrosive environments for a long time. Their anti-corrosion performance is directly related to the stability and safety of the entire system. Therefore, developing a highly tough, non-shedding anti-corrosion material is crucial to ensure the long-term operation of steel flues.
[0003] Traditional steel flue anti-corrosion materials mainly include FRP, rubber, glass flakes, acid-resistant mastic, etc. These materials have anti-corrosion properties to a certain extent, but there are still many deficiencies in practical applications. For example, although FRP anti-corrosion materials have a smooth surface, are wear-resistant and acid-resistant, they have a low elastic modulus, poor long-term temperature resistance, and are not resistant to aging; rubber anti-corrosion materials such as silicone rubber and polyurea have good waterproof and acid resistance, but poor high temperature resistance and insufficient wear resistance; glass flake anti-corrosion materials have good heat and acid resistance, but poor adhesion and are easy to fall off in pieces; acid-resistant mastic anti-corrosion materials have good heat and acid resistance, but poor waterproof and moisture resistance, and are easy to absorb moisture from flue gas, causing powdering and falling off.
[0004] With the advancement of science and technology, some new anti-corrosion materials have emerged in recent years, such as polymer composite materials and inorganic non-metallic materials. These materials have significantly improved their anti-corrosion performance, but there are still some problems. For example, although polymer composite materials have excellent corrosion resistance, they are relatively expensive, and their long-term stability in high temperature environments still needs to be further verified; inorganic non-metallic materials such as ceramics, although they are resistant to high temperatures and corrosion, are brittle and lack toughness, and are difficult to withstand large mechanical stresses.
[0005] In addition, many existing anti-corrosion materials have the problem of insufficient adhesion. Especially in high temperature, high pressure and corrosive environment, the material is easy to fall off from the surface of the steel flue, resulting in a significant reduction in the anti-corrosion effect. This not only shortens the service life of the steel flue, but also may cause pollution to the surrounding environment. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a high-toughness anti-corrosion coating composition that does not fall off.
[0009] In order to solve the above technical problems, the present invention provides the following technical solution: based on the mass fraction of raw materials, it comprises:
[0010] 50-100 parts of phenolic epoxy resin, 5-20 parts of nano titanium powder, 10-30 parts of silicon carbide, 3-7 parts of cardanol glycidyl ether, 5-10 parts of glass flakes, 1-5 parts of cardanol modified polyamine curing agent, and 1-5 parts of auxiliary agent.
[0011] Preferably, the auxiliary agent includes one or more of an anti-settling agent, a leveling agent, and a defoaming agent.
[0012] Preferably, the nano titanium powder is 10 to 15 parts.
[0013] Preferably, the silicon carbide is 20 to 25 parts.
[0014] Preferably, the amount of cardanol glycidyl ether is 3 to 5 parts.
[0015] Preferably, the glass flakes are 5 to 8 parts.
[0016] Preferably, the cardanol-modified polyamine curing agent is 3 to 5 parts.
[0017] Another object of the present invention is to provide a method for preparing a non-shedding high-toughness anti-corrosion coating composition.
[0018] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0019] The phenolic epoxy resin, nano titanium powder, silicon carbide and glass flakes are uniformly stirred and dispersed to obtain a mixture I;
[0020] Add cardanol glycidyl ether to mixture I and stir until completely mixed to obtain mixture II;
[0021] Adding cardanol modified polyamine curing agent and auxiliary agent to mixture II and stirring to obtain mixture III;
[0022] The mixture III is ground to an average particle size of 5 to 150 microns, and filtered to obtain a non-shedding high-toughness anti-corrosion material for a steel flue.
[0023] As a preferred embodiment of the method for preparing the non-shedding high-toughness anti-corrosion coating composition of the present invention, the stirring temperature is 40-50° C. and the stirring time is 4-12 hours.
[0024] Another object of the present invention is to provide a non-shedding high-toughness anti-corrosion coating composition for use in steel flue corrosion protection.
[0025] Beneficial effects of the present invention:
[0026] The invention provides a non-shedding high-toughness anti-corrosion coating composition. By designing and optimizing the formula, a synergistic effect is achieved between the raw materials. The long-chain structure of the cardanol-modified polyamine curing agent and the synergistic effect with the phenolic epoxy resin enable the cured product to have a greater degree of freedom when subjected to external force, thereby improving its toughness. The addition of nano-titanium powder, silicon carbide and glass flakes, as well as the corrosion resistance of the cardanol-modified polyamine curing agent itself, together constitute an effective anti-corrosion system, which significantly improves the corrosion resistance of the cured product. The flaky structure of the glass flakes can form a mechanical locking effect, while the flexibility and reactive functional groups of the cardanol-modified polyamine curing agent are helpful to form a good chemical bond with a substrate, thereby enhancing the adhesion of the cured product. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art, specifically:
[0030] The phenolic epoxy resin used in the present invention is liquid phenolic epoxy resin F51:
[0031] The cardanol-modified polyamine curing agent used in the present invention is synthesized by using cardanol as a raw material through Mannich reaction and water-based treatment according to the existing method. Specifically:
[0032] Epoxy resin E51 and PEG600 were mixed in a molar ratio of 1:2, heated in a constant temperature water bath at 90°C to melt and stirred evenly for 30 minutes, and 3 wt.% of boron trifluoride ether complex relative to the total system was added dropwise in batches, and reacted at a constant temperature for 2 hours to form a transparent emulsion to obtain epoxy-terminated polyethylene glycol EP;
[0033] Cardanol and triethylenetetramine are mixed in a mass ratio of 100:60, heated in a water bath at 70°C for 30 minutes, and a formaldehyde solution having a mass fraction of 30% relative to the mass of cardanol is added dropwise, and then the mixture is heated to 100°C for reaction for 3 hours, washed, and dehydrated by reduced pressure distillation to obtain cardanol aldehyde amine MA;
[0034] 100 parts of cardanol aldehyde amine MA, 15 parts of polyethylene glycol EP and 2 parts of (3-glycidyl propoxy) trimethoxy silane were mixed, heated in a water bath at 70°C and stirred for 60 minutes. After the temperature dropped to 60°C, deionized water was added dropwise through a constant pressure dropping funnel. After the addition was completed in 30 minutes, stirring was continued for 30 minutes to obtain a cardanol-modified polyamine curing agent.
[0035] The anti-corrosion performance of the high-toughness anti-corrosion material prepared by the present invention is determined by a high-temperature corrosion test, specifically:
[0036] The anti-corrosion materials prepared in each embodiment / comparative example were sprayed onto 20# carbon steel (the same below). The surface of the coating sample was coated with a salt solution of NaCl and Na2SO4 mixed in a mass ratio of 1:3, and the coating amount was 2 mg / cm 2 , obtain the sample to be tested and record the initial weight;
[0037] The sample to be tested is placed in a tubular furnace, and argon is flushed into the furnace. The heating rate is 4℃ / min. After heating to 600℃, the reaction gas is flushed in with a gas flow rate of 20ml / min. A simulated flue gas corrosion experiment is carried out. After reacting for 40 hours, the sample is taken out (cooled to room temperature and taken out) and weighed, and the weight gain per unit area of the sample is recorded. During this reaction time, the higher the weight gain, the worse the corrosion resistance, and the lower the weight gain, the better the corrosion resistance.
[0038] The adhesion test method refers to the standard GB / T8642-1988, and the impact toughness is determined by referring to the standard GBT1451-2005.
[0039] Example 1
[0040] This embodiment provides a method for preparing a non-shedding high-toughness anti-corrosion coating composition, specifically:
[0041] 1) Weigh the raw materials according to the following formula:
[0042] 70 parts of phenolic epoxy resin, 15 parts of nano titanium powder, 20 parts of silicon carbide, 5 parts of cardanol glycidyl ether, 5 parts of glass flakes, 3 parts of cardanol modified polyamine curing agent, 1 part of organic bentonite (anti-settling agent), 1 part of MSD-910 (polyether modified polysilicone oxygen leveling agent), 1 part of MSD-201 (dimethyl silicone oil defoaming agent);
[0043] 2) The phenolic epoxy resin, nano titanium powder, silicon carbide and glass flakes are uniformly stirred and dispersed at 40° C. to obtain a mixture I;
[0044] Adding cardanol modified epoxy diluent to mixture I and stirring at 40° C. until completely mixed to obtain mixture II;
[0045] Add the cardanol-modified polyamine curing agent and the auxiliary agent to the mixture II and stir at 40° C. to obtain a mixture III;
[0046] The mixture III was ground to an average particle size of 80 microns, and filtered to obtain a non-shedding high-toughness anti-corrosion coating composition.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that the nano titanium powder is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the anti-corrosion coating composition of this comparative example.
[0049] Comparative Example 2
[0050] The difference between this comparative example and Example 1 is that silicon carbide is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the anti-corrosion coating composition of this comparative example.
[0051] Comparative Example 3
[0052] The difference between this comparative example and Example 1 is that the cardanol-modified epoxy diluent is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the anti-corrosion coating composition of this comparative example.
[0053] Comparative Example 4
[0054] The difference between this comparative example and Example 1 is that the cardanol-modified polyamine curing agent is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the anti-corrosion coating composition of this comparative example.
[0055] The performance of the anti-corrosion coating composition prepared by the comparative example 1 and comparative examples 1 to 4 according to the above method is shown in Table 1.
[0056] Table 1 Comparison of the properties of the anticorrosive coating compositions prepared in Example 1 and Comparative Examples 1 to 4
[0057] <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 ).]]> Example 1 1.5 60.5 208 Comparative Example 1 5.9 54.2 186 Comparative Example 2 4.2 55.4 192 Comparative Example 3 3.3 36.8 175 Comparative Example 4 6.1 38.5 154
[0058] It can be seen from Table 1 that omitting the nano titanium powder, silicon carbide, cardanol-modified epoxy diluent, and cardanol-modified polyamine curing agent in the present invention will have a significant impact on the performance of the obtained anti-corrosion material.
[0059] Nano titanium powder has extremely strong corrosion resistance and can significantly improve the anti-corrosion performance of the coating when added to the coating. Its nano effect can fill the structural micropores generated when the coating is cured, reduce capillary action, and isolate the passage between the protected substrate and the outside world, thereby improving the barrier performance of the coating. At the same time, the flaky structure of nano titanium powder can produce a "maze effect" to extend the path for the corrosive medium to penetrate into the substrate. If nano titanium powder is omitted, the anti-corrosion performance of the coating will be significantly reduced because the key components for improving the barrier performance of the coating and extending the penetration path of the corrosive medium are missing.
[0060] Silicon carbide has good corrosion resistance to acids, alkalis and other chemical substances, and can be used stably for a long time in harsh chemical environments. Adding it to anti-corrosion coatings can enhance the corrosion resistance and service life of the coatings. If silicon carbide is omitted, the corrosion resistance of the coating will be greatly affected, especially in acidic and alkaline environments, the corrosion resistance of the coating will be significantly reduced.
[0061] Cardanol modified epoxy diluent has the characteristics of excellent dilution ability, fast curing, fast hardness growth rate and good stability. It can not only reduce the viscosity of the coating, improve the fluidity of the coating, but also enhance the water resistance and chemical corrosion resistance of the coating. Cardanol modified epoxy diluent has excellent adhesion performance and can significantly improve the bonding strength between the coating and the substrate. After omitting the cardanol modified epoxy diluent, the adhesion will be significantly reduced.
[0062] Cardanol modified polyamine curing agent is a curing agent with excellent performance. It combines the hardness and chemical corrosion resistance of fatty amine system, the long-term applicability and good toughness of polyamide system, and the rapid curing and excellent adhesion of phenolic amine system. After omitting the cardanol modified polyamine curing agent, the curing speed and curing degree of the coating will be affected, thereby affecting the anti-corrosion performance of the coating. Because the incompletely cured coating is more susceptible to erosion by the corrosive medium, the bonding strength with the substrate will also be weakened.
[0063] Example 2
[0064] The difference between this embodiment and embodiment 1 is that the mass fractions of nano titanium powder are adjusted to 5, 10, 15, 20 and 25 parts respectively, and the remaining steps and processes are referred to embodiment 1 to obtain the anti-corrosion coating composition of this embodiment. The relevant properties are measured according to the above method, and the results are shown in Table 2.
[0065] Table 2 Comparison of properties of anticorrosive coating compositions prepared with different contents of nano titanium powder
[0066] Nano titanium powder / parts <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> 5 3.2 48.1 168 10 1.9 58.6 197 15 1.5 60.5 208 20 2.0 47.8 156 25 3.7 32.9 150
[0067] As can be seen from Table 2, the mass fraction of nano titanium powder has a significant effect on the performance of the anti-corrosion material. Although nano titanium powder can significantly improve the anti-corrosion performance of the coating, too high a content may cause the dispersion of nanoparticles in the coating to deteriorate and agglomerate. This will reduce the interfacial compatibility between nano titanium powder and matrix materials such as resin, thereby affecting the overall anti-corrosion effect of the coating. When the content of nano titanium powder is too high, the pores in the coating may be overfilled, causing the coating to become too dense, which in turn affects the diffusion path of the corrosive medium, making the coating more susceptible to corrosion under certain conditions.
[0068] Although the addition of nano titanium powder can enhance the hardness and wear resistance of the coating to a certain extent, too high a content may cause the coating to become brittle and hard, and its toughness decreases. This is because the interaction between nano titanium powder and matrix materials such as resin is enhanced, making the coating more likely to break when impacted by external forces. On the other hand, if the interaction between nano titanium powder and matrix materials such as resin is too strong, it may cause internal stress in the coating during the curing process, thereby affecting adhesion.
[0069] Example 3
[0070] The difference between this embodiment and embodiment 1 is that the mass fractions of silicon carbide are adjusted to 5, 10, 20, 25, and 30 parts respectively, and the remaining steps and processes are referred to embodiment 1 to obtain the anti-corrosion coating composition of this embodiment. The relevant properties are measured by referring to the above method, and the results are shown in Table 3.
[0071] Table 3 Comparison of properties of anticorrosive coating compositions prepared with different contents of silicon carbide
[0072] Silicon carbide / parts <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> 5 4.8 42.3 156 10 2.5 49.8 167 20 1.5 60.5 208 25 1.9 51.6 201 30 3.1 43.2 188
[0073] As can be seen from Table 3, adjusting the mass fraction of silicon carbide has a significant impact on the performance of the obtained material. Silicon carbide powder itself has the characteristics of high hardness and high strength, but when its content is too high, it may cause the material as a whole to become too brittle and hard, and reduce the toughness of the material. This will affect the material's ability to resist deformation when subjected to force, and may cause the material to break more easily when subjected to impact or pressure.
[0074] In addition, silicon carbide powder has good stability at high temperatures and can enhance the thermal shock resistance of the material. However, too high a content may increase the internal stress of the material, which in turn reduces its thermal shock resistance. This is because the difference in thermal expansion coefficient between silicon carbide powder and the matrix material may cause thermal stress when the temperature changes, thus affecting the overall performance of the material.
[0075] Example 4
[0076] The difference between this embodiment and embodiment 1 is that the mass fractions of cardanol glycidyl ether are adjusted to 1, 3, 5, 7, and 9 parts respectively, and the remaining steps and processes are referred to embodiment 1 to obtain the anti-corrosion coating composition of this embodiment, and the relevant properties are measured by referring to the above method. The results are shown in Table 4.
[0077] Table 4 Comparison of properties of anticorrosive coating compositions prepared with different contents of cardanol glycidyl ether
[0078] Cardanol Glycidyl Ether / Parts <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> 1 3.4 46.8 163 3 2.1 56.1 199 5 1.5 60.5 208 7 2.3 55.5 187 9 3.6 43.8 165
[0079] As can be seen from Table 4, adjusting the mass fraction of cardanol glycidyl ether has a significant effect on the performance of the obtained material. In the present invention, cardanol glycidyl ether is used as a diluent, and its main function is to reduce the viscosity of the material and improve fluidity. However, when the content is too high, although the viscosity will be further reduced, it may cause the material to be too thin, affecting the construction performance and the mechanical strength after curing.
[0080] In addition, cardanol glycidyl ether contains epoxy groups, which can participate in the curing reaction. Too high a content will accelerate the curing process, which may lead to incomplete curing or excessive curing heat, thus affecting the overall performance of the material.
[0081] Example 5
[0082] The difference between this embodiment and embodiment 1 is that the mass fractions of the cardanol-modified polyamine curing agent are adjusted to 1, 3, 5, 7, and 9 parts respectively, and the remaining steps and processes are referred to embodiment 1 to obtain the anti-corrosion coating composition of this embodiment. The relevant properties are measured by referring to the above method, and the results are shown in Table 5.
[0083] Table 5 Comparison of properties of anticorrosive coating compositions prepared with different contents of cardanol-modified polyamine curing agents
[0084] Cardanol modified polyamine curing agent / parts <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> 1 2.1 58.3 189 3 1.5 60.5 208 5 1.8 59.1 192 7 2.5 56.2 183 9 3.6 49.3 166
[0085] It can be seen from Table 5 that adjusting the mass fraction of the cardanol-modified polyamine curing agent has a significant effect on the performance of the obtained material. The cardanol-modified polyamine curing agent contains active amino groups that can react with the epoxy groups in the epoxy resin to promote curing. However, when the curing agent content is too high, the curing speed will be accelerated, which may cause the curing reaction to be too violent, generate too much curing heat, and affect the overall performance of the material.
[0086] In addition, an increase in the curing agent content usually increases the hardness of the curing system. However, the flexible groups in the cardanol-modified polyamine curing agent (such as the long-chain alkanes of cardanol) also give the material a certain toughness. When the curing agent content is too high, the hardness may increase significantly, but the toughness may decrease, causing the material to become brittle and hard. An appropriate amount of curing agent can improve the adhesion between the curing system and the substrate and the bonding strength within the system. However, when the curing agent content is too high, the internal stress of the curing system may increase due to the rapid curing reaction, which in turn reduces the adhesion. At the same time, too high a curing agent content may also lead to uneven distribution of bonding strength within the system, resulting in a decrease in local strength.
[0087] Example 6
[0088] The difference between this embodiment and embodiment 1 is that the nano titanium powder is adjusted to equal masses of nano silicon dioxide, nano aluminum oxide, and nano zirconium oxide, and the remaining steps and processes are referred to embodiment 1 to obtain the anti-corrosion coating composition of this embodiment. The relevant properties are measured according to the above method, and the results are shown in Table 6.
[0089] Table 6 Comparison of performance of anticorrosive coating compositions made from different types of nanomaterials
[0090] <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> Nano titanium powder 1.5 60.5 208 Nano Silica 2.2 43.6 167 Nano Alumina 3.9 44.7 172 Nano Zirconia 3.5 36.1 170
[0091] As can be seen from Table 6, the selection of nano titanium powder in the present invention has significant advantages over the selection of other nano materials with anti-corrosion properties. This is because the nano titanium powder has a high degree of corrosion resistance and oxidation resistance, and can form a solid titanium oxide layer on the surface of the coating. This titanium oxide layer has extremely high chemical stability and corrosion resistance, and can effectively prevent the corrosion of the coating by corrosive substances. In addition, the nano titanium powder also has photocatalytic properties, which can decompose organic pollutants on the surface of the coating and further protect the coating from corrosion. Compared with other materials, which are mainly achieved by improving the hardness and chemical resistance of the coating, the nano titanium powder can provide more comprehensive anti-corrosion protection. Compared with other materials, the nano titanium powder has extremely high surface energy, can form a strong bond with the coating substrate, and improve the adhesion of the coating. Its uniform dispersion in the coating also helps to improve the interfacial bonding between the coating and the substrate.
[0092] Example 7
[0093] The difference between this embodiment and embodiment 1 is that the cardanol glycidyl ether is adjusted to equal masses of alkylene glycidyl ether, polypropylene glycol diglycidyl ether, acetone, and ethyl acetate, and the remaining steps and processes are referred to embodiment 1 to obtain the anti-corrosion coating composition of this embodiment. The relevant properties are measured by referring to the above method, and the results are shown in Table 7.
[0094] Table 7 Comparison of properties of anticorrosive coating compositions prepared with different types of diluents
[0095] <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> Cardanol Glycidyl Ether 1.5 60.5 208 Alkylene glycidyl ether 2.4 53.1 176 Polypropylene glycol diglycidyl ether 1.9 55.6 178 acetone 6.2 40.4 122 Ethyl acetate 5.2 42.1 145
[0096] As can be seen from Table 7, the selection of cardanol glycidyl ether in the present invention has significant advantages over the selection of other diluents. Cardanol glycidyl ether is used as a diluent / toughening agent, and its long aliphatic hydrocarbon chain can play a buffering role in the epoxy resin curing process, absorb external stress, thereby improving the toughness of the coating. This toughening effect helps the coating to be difficult to crack or peel off when subjected to external forces, improves the overall durability of the coating, and has good compatibility with phenolic epoxy resin, and can form a uniform mixed system. This compatibility helps to ensure the uniform distribution of cardanol glycidyl ether in epoxy resin, thereby giving full play to its dilution and toughening effect.
[0097] Furthermore, cardanol glycidyl ether, as a diluent and toughening agent, can improve the dispersibility of nano-titanium powder in the coating, making it more evenly distributed in the coating, thereby improving the overall anti-corrosion performance of the coating. The addition of cardanol glycidyl ether can also improve the interfacial bonding force between silicon carbide particles and the epoxy resin matrix, making the silicon carbide particles more firmly embedded in the coating, thereby improving the overall strength and wear resistance of the coating.
[0098] The cardanol-modified polyamine curing agent can react with the epoxy groups in the phenolic epoxy resin to form a cross-linked network structure. The epoxy groups in cardanol glycidyl ether can also participate in this reaction process, further promoting the curing of the coating. At the same time, the flexible groups of cardanol glycidyl ether can improve the adhesion between the coating and the substrate, and improve the overall adhesion and durability of the coating. That is, the reason why cardanol glycidyl ether has a significant advantage over other diluents in this formulation system is its unique chemical structure and properties and its synergistic effects with other raw materials in the system. These synergistic effects jointly improve the toughness, corrosion resistance, adhesion and other properties of the coating.
[0099] Example 8
[0100] The difference between this embodiment and Example 1 is that the cardanol-modified polyamine curing agent is adjusted to equal masses of diethylenetriamine, meta-phenylenediamine, hexamethylenetetramine, and bismaleimide, and the remaining steps and processes are all referred to Example 1 to obtain the anti-corrosion coating composition of this embodiment. The relevant properties are measured by referring to the above method, and the results are shown in Table 8.
[0101] Table 8 Comparison of properties of anticorrosive coating compositions prepared with different types of cardanol-modified polyamine curing agents
[0102] <![CDATA[Corrosion resistance / mg / cm 2 > Adhesion / MPa <![CDATA[Impact toughness (KJ / m 2 )]]> Cardanol Glycidyl Ether 1.5 60.5 208 Diethylenetriamine 3.5 53.1 177 m-Xylylenediamine 4.6 56.2 167 Hexamethylenetetramine 4.1 44.1 143 Bismaleimide 5.0 34.6 150
[0103] As can be seen from Table 8, the selection of cardanol-modified polyamine curing agent in the present invention has significant advantages over the selection of other diluents. The phenolic epoxy resin itself has excellent mechanical properties. The phenolic hydroxyl group and amine group in the cardanol-modified polyamine curing agent can react with the epoxy group in the epoxy resin to form a three-dimensional cross-linked network structure, thereby improving the strength and toughness of the cured product. The long-chain structure of the cardanol-modified polyamine curing agent helps to isolate the rigid benzene ring in the epoxy resin molecule, so that its macromolecular chain still has a large degree of freedom when an external force acts, further improving the flexibility of the cured product.
[0104] In addition, the long chain structure of the cardanol-modified polyamine curing agent can form a better coating and dispersion effect with the nano-titanium powder, thereby improving the utilization rate of the nano-titanium powder in the system and the overall performance of the cured product. The cardanol-modified polyamine curing agent reacts with the epoxy group in the cardanol glycidyl ether, which can further enhance the cross-linking density and toughness of the cured product. At the same time, the long chain structure of cardanol also helps to improve the flexibility and heat resistance of the cured product.
[0105] That is, the reason why the cardanol-modified polyamine curing agent has significant advantages in this formulation system is its unique molecular structure and excellent performance characteristics, as well as the synergistic effect with other raw materials in the system. These synergistic effects jointly improve the toughness, corrosion resistance and adhesion of the cured product.
[0106] In summary, the present invention provides a non-shedding high-toughness anti-corrosion material for steel flues. By designing and optimizing the formula, a synergistic effect is achieved between the raw materials. The long-chain structure of the cardanol-modified polyamine curing agent and the synergistic effect with the phenolic epoxy resin allow the cured product to have a greater degree of freedom when subjected to external forces, thereby improving its toughness. The addition of nano-titanium powder, silicon carbide and glass flakes, as well as the corrosion resistance of the cardanol-modified polyamine curing agent itself, together constitute an effective anti-corrosion system, which significantly improves the corrosion resistance of the cured product. The flaky structure of the glass flakes can form a mechanical locking effect, and the flexibility and reactive functional groups of the cardanol-modified polyamine curing agent help to form a good chemical bond with the substrate, thereby enhancing the adhesion of the cured product.
[0107] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A non-shedding high-toughness anti-corrosion coating composition, characterized in that: Calculated by mass of raw materials, including: 50-100 parts of phenolic epoxy resin, 10-15 parts of nano titanium powder, 20-25 parts of silicon carbide, 3-5 parts of cardanol glycidyl ether, 5-10 parts of glass flakes, 3-5 parts of cardanol modified polyamine curing agent, and 1-5 parts of auxiliary agent.
2. The non-shedding high-toughness anti-corrosion coating composition according to claim 1, characterized in that: The auxiliary agent includes one or more of an anti-settling agent, a leveling agent, and a defoaming agent.
3. The non-shedding high-toughness anti-corrosion coating composition according to claim 1, characterized in that: Calculated by the mass percentage of the raw materials of the high-toughness anti-corrosion coating composition, the glass flakes are 5 to 8 parts.
4. The method for preparing the non-shedding high-toughness anticorrosive coating composition according to any one of claims 1 to 3, characterized in that: include, The phenolic epoxy resin, nano titanium powder, silicon carbide and glass flakes are uniformly stirred and dispersed to obtain a mixture I; Add cardanol glycidyl ether to mixture I and stir until completely mixed to obtain mixture II; Adding cardanol modified polyamine curing agent and auxiliary agent to mixture II and stirring to obtain mixture III; The mixture III is ground to an average particle size of 5 to 150 microns, and filtered to obtain a non-shedding high-toughness anti-corrosion coating composition for steel flues.
5. The method for preparing the non-shedding high-toughness anti-corrosion coating composition according to claim 4, characterized in that: The stirring temperature is 40-50° C. and the stirring time is 4-12 h.
6. Use of the non-shedding high-toughness anti-corrosion coating composition as described in any one of claims 1 to 3 in the anti-corrosion of steel flues.
Citation Information
Patent Citations
Low-viscosity cardanol solidifying agent of epoxy resin and preparation method thereof
CN101319042A
Solvent-free epoxy primer for high temperature corrosion prevention of steel pipeline welded junction position
CN102382553A
Temperature-resistant acid-resistant anticorrosive coating for steel structure reaction kettle lining
CN111040584A
Temperature-resistant and corrosion-resistant coating and preparation method thereof
CN113278343A